Measles vaccines designed for enhanced CD8+ T cell activation - Busch, Elena; Kubon, Kristina Dorothea; Mayer, Johanna K. M.; Pidelaserra Martí, Gemma; Albert, Jessica; Hoyler, Birgit; Heidbüchel, Johannes P. W.; Stephenson, Kyle B.; Lichty, Brian D.; Osen, Wolfram; Eichmüller, Stefan B.; Jäger, Dirk; et al. (Viruses, 2020)
Priming and activation of CD8+ T cell responses is crucial to achieve anti-viral and anti-tumor immunity. Live attenuated measles vaccine strains have been used successfully for immunization for decades and are currently investigated in trials of oncolytic virotherapy. The available reverse genetics systems allow for insertion of additional genes, including heterologous antigens. Here, we designed recombinant measles vaccine vectors for priming and activation of antigen-specific CD8+ T cells. For proof-of-concept, we used cytotoxic T lymphocyte (CTL) lines specific for the melanoma-associated differentiation antigen tyrosinase-related protein-2 (TRP-2), or the model antigen chicken ovalbumin (OVA), respectively. We generated recombinant measles vaccine vectors with TRP-2 and OVA epitope cassette variants for expression of the full-length antigen or the respective immunodominant CD8+ epitope, with additional variants mediating secretion or proteasomal degradation of the epitope. We show that these recombinant measles virus vectors mediate varying levels of MHC class I (MHC-I)-restricted epitope presentation, leading to activation of cognate CTLs, as indicated by secretion of interferon-gamma (IFNγ) in vitro. Importantly, the recombinant OVA vaccines also mediate priming of naïve OT-I CD8+ T cells by dendritic cells. While all vaccine variants can prime and activate cognate T cells, IFNγ release was enhanced using a secreted epitope variant and a variant with epitope strings targeted to the proteasome. The principles presented in this study will facilitate the design of recombinant vaccines to elicit CD8+ responses against pathogens and tumor antigens.
Gesehen am 21.04.2020